Adaptation of 5S Culture in Forming the Character of Grade 1 Students Based on Islamic and Muhammadiyah Values: An Ethnographic Study at Muhammadiyah Elementary School 34 Cikupa - Rosmiati, Rosmiati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The tran sition period from family environment to elementary school is an important phase in student character building. This study aims to understand how the adaptation of the 5S culture (Smile, Salam, Sapa, Polite, and Santun) can shape the character of grade 1 students integrated with Al-Islam and Kemuhammadiyahan (AIK) values. The research method used a qualitative approach with ethnographic methods at SD Muhammadiyah 34 Cikupa, involving 28 students, teachers, and parents. Data collection techniques included six months of participatory observation, in-depth interviews, visual documentation, and field notes. The results show that there are three stages of 5S culture adaptation, namely the stages of imitation, internalization, and naturalization. The 5S culture proved effective in instilling AIK values early on, marked by a significant increase in students' positive behavior. This process is influenced by the child's personality, family involvement, and teacher exemplary. The integration of 5S culture and AIK can be an effective strategy in Islamic character education, especially in the early transition period of elementary school.